Perspetivas Didáticas e Metodológicas no Ensino Básico - José Luís Gonçalves (Escola Superior de Educação de Paula Frassinetti, 2015)
The history of educational thought attests the slow and sustained effort made by many educators in updating the methods and the process of teaching, towards the child's perspective and the appreciation of the role of the teacher, helping to devise a theoretical and practical distinction between the concepts of "teaching", "education", "instruction" and "training". If, in pursuit of this goal, Pedagogy has conquered its own scientific autonomy in the nineteenth century, separating itself especially from Philosophy, Didactics would emancipate itself only later and justly against Pedagogy, rejecting to remain an auxiliary matter. Didactics had to settle then against the sectarianism of the curriculum design advocates who supported a forced convergence between Curriculum and Didactics. As one can remember, in the decades of the years 20-50 of the last century, Didactics initially surrendered to the dictates of the New School, in reaction to the Traditional School. From the 60s and 70s, criticisms of that dominant postulate of alleged anthropological-educational neutrality grow, giving rise to didactic models based on a mixed paradigm, sometimes of humanist traits, sometimes of techno-scientific matrix. For the humanist trait of Didactics, decisively contributed the studies of Psychology and the priority given to inter-subjective relationship established in the educational act; the techno-scientific framework that framed Didactics during this stage was supported theoretically on the valuation of the intentionality of the educational process as a dynamic activity, systematic, effective and favoring the objective and subjective conditions which facilitate student learning. In any case, the discovery of the complexity and multidimensionality of the teaching-learning process has created the necessary basis so that Didactics is claimed as debtor of a transdisciplinary knowledge base. In the 80s and 90s of the twentieth century, Didactics continued under strong scientific scrutiny since, once stabilized its concept and subject matter, as well as identified it corpus of knowledge, it seemed not to be still satisfactorily implemented the research methods of practice as reflection and the analysis, altogether, of the teaching-learning process and teacher education as a whole. So when, in 1994, Isabel Alarcão proposed the "didactic triptych" (investigative teaching, curriculum and professional teaching didactics) as conceptual referential guiding the construction of didactic knowledge of teachers, she intended to promote a transformation of these educational praxis. At the beginning of this century, and under the auspices of this drive, the same author notes that didactic research has already produced some impact on the professional didactics of teachers, though other researchers recognize teachers still an incipient role in the production and dissemination of didactical knowledge. Such a delay may be explained in part by the absence and / or invisibility of teachers in the role of participating researchers who innovate their practices. To overcome this gap, Flavia Vieira argues for the centrality of experience in the processes of (trans) formation of teacher training in the construction of knowledge, so that the regional dimension of teaching is instituted as a development axis of its formative dimension. Now, as reflex - or maybe not - of the present times, this issue of the magazine Saber & Educate, subject to the theme "Methodological and didactical perspectives in Basic Education", gathers an unusually high number of articles. The positive response that this call for articles had among the scientific community attests, in our view, the relevance of the topic and underlined the disciplinary plurality of articles now published, it witness the competency of research undertaken by teachers, whether in higher education or not, who produce didactically relevant and useful knowledge. Thus, it is proved that, given the diversity of anthropological models that provide foundation to the educational action and the education conceptions underlying them, the educational work is investing in the rationality of the educational process translated into a professional didactic able to provide both student learning, trans / formation / in the teaching praxis and construction of the professional identity of the teacher. These unremitting efforts of critical vigilance over the action in formal school context should be translated, moreover, into effective student learning. If "professional incompetence disqualifies the teacher's authority" (Paulo Freire), it will be in this reconstruction of the professional identity of teachers that will reside the eradication of the stigma that a "bad" teacher is a worker chief of social exclusion through school failure from the students. Finally, a word of thanks to national and international experts invited, for the distinctive articles sent to this thematic issue. With this initiative, the Saber & Educate magazine wanted to bring the public the best of what we have produced in the field of didactics and teacher training. To everyone our appreciation for the increased quality brought to this edition, in addition to the valuable contributions of the authors of articles now available.